ZAKAT PRODUKTIF SEBAGAI SALAH SATU SOLUSI PENGENTASAN KEMISKINAN DAN PENGANGGURAN DI INDONESIA - ELFADHLI ELFADHLI (JURIS (Jurnal Ilmiah Syariah), 2016)
Indonesia, as one of the majority Moslem population in the world, is potentially promising for the growth and the development of zakah (divine tax) program, especially property, and to be made more productive, both in terms worships and practices of Islamic values, and economic activities in general. By means of zakah raising institution (BAZ), the process of raising and distributing of zakah will be more effective and guaranteed. Furthermore, zakah is believed to be able to solve problems dealing with poverty resulting from the increase numbers of unemployement. Productive zakah, for example, give an opportunity for the zakah receivers to make use the money or property to start a new better life.Kata kunci:  productive tithe/zakah, distribution, unemployment , eradicate poverty